Pengaruh Budaya Nasional Terhadap Kualitas Audit Internal Pada Sektor Pendidikan Tinggi Di Indonesia - Andrew Krishna Putra; Yusuf, Muhammad (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2024)
This research investigates the influence of national culture on the quality of internal audits in the higher education sector in Indonesia. This research uses a national culture model developed by Hofstede using 3 cultural dimensions: power distance, uncertainty avoidance, and individualism. Research related to this topic is still very minimal in Indonesia, especially when it is related to the internal audit function in universities. alone can have an impact on increasing the effectiveness of the university's internal supervisory unit. The unit of analysis for this research is a university located in the LLDIKTI III working area considering the strategic location of this area as an agglomeration of business, government and education centers in Indonesia. Data was obtained using survey techniques which were distributed to the Head of the Internal Audit Unit as the work unit responsible for internal audit. This research uses covariance based-SEM techniques to test the hypotheses developed. The result is that uncertainty avoidance has a significant negative effect on internal audit quality, while power distance and individualism do not have a significant effect on internal audit quality. This means that the lower the uncertainty avoidance, the higher the internal audit quality and vice versa, while power distance and individualism do not have a significant effect on internal audit quality.